A low‐profile wide‐scanning fully metallic lens antenna for 5G communication. Issue 5 (17th February 2021) - Liu, Kunning; Yang, Shiwen; Qu, Shi‐Wei; Chen, Yikai; Huang, Ming; Hu, Jun
Abstract: A low‐profile wide‐scanning lens antenna operating at 5G millimeter‐wave (mm‐wave) frequencies (24‐29 GHz) is presented in this article. Based on the principles of parallel plate waveguide, the proposed lens consists of two almost‐parallel plates which have only one slot or ridge in their inner surfaces. Due to that the lens is filled with air, the prominent high loss of dielectric lens at mm‐wave frequencies can be avoided. The 22 monopole antennas are employed to feed the lens, providing over ±77° beam scanning coverage of −3 dB cross‐over level in the azimuth plane. Measured 3 dB beamwidths are 7°/69° in the azimuth/elevation plane at the middle frequency of 26.5 GHz, respectively. Measured aperture efficiency for the middle beam is 66% at 26.5 GHz, and varies between 40% and 69.4% over the operating frequency band. The results indicate that the proposed lens is an effective solution for the 5G wireless communications due to its wide‐angle scanning, lightweight, low cost, and easy fabrication.